Neurophysiological correlates of memory change in children with fetal alcohol spectrum disorders treated with choline - Fuglestad, Anita J.; Miller, Neely C.; Fink, Birgit A.; Boys, Christopher J.; Eckerle, Judith K.; Georgieff, Michael K.; Wozniak, Jeffrey R. (Frontiers in Psychology, 2022)
Background Prenatal and early postnatal choline supplementation reduces cognitive and behavioral deficits in animal models of Fetal Alcohol Spectrum Disorder (FASD). In a previously published 9-month clinical trial of choline supplementation in children with FASD, we reported that postnatal choline was associated with improved performance on a hippocampal-dependent recognition memory task. The current paper describes the neurophysiological correlates of that memory performance for trial completers. Methods Children with FASD (N = 24) who were enrolled in a clinical trial of choline supplementation were followed for 9 months. Delayed recall on a 9-step elicited imitation task (EI) served as the behavioral measure of recognition memory. Neurophysiological correlates of memory were assessed via event-related potentials (ERP). Results Delayed recall on EI was correlated with two ERP components commonly associated with recognition memory in young children: middle latency negative component (Nc amplitude; range: r = −0.41 to r = −0.44) and positive slow wave (PSW area under the curve; range: r = −0.45 to r = −0.63). No significant ERP differences were observed between the choline and placebo groups at the conclusion of the trial. Conclusion Although the small sample size limits the ability to draw clear conclusions about the treatment effect of choline on ERP, the results suggest a relationship between memory performance and underlying neurophysiological status in FASD. This trial was registered.1